Cassava and overcoming the challenges of global climatic change: report of the second scientific conference of the Global Cassava Partnership for the 21st century - Hyman, Glenn G.; Bellotti, Anthony C.; Becerra López Lavelle, Luis Augusto; Palmer, Neil; Creamer, Bernardo (Springer, 2012)
Tropical agriculture must feed a growing population under increasingly challenging environmental conditions. Cassava has particularly critical roles to play. It is the third-most important tropical crop after rice and maize, providing livelihoods and food security for hundreds of millions of people. To address challenges for cassava improvement, the Global Cassava Partnership for the 21st Century (GCP21) held its second scientific meeting in Kampala, Uganda, from 19–23 June, 2012. Hosted by the government of Uganda, the conference brought together over 400 scientists and professionals working on various aspects of cassava improvement.